Diskursus Hukum Kewarisan ‘An-Tarâdhin: Menjembatani Dialektika Kewarisan Maternalistik dan Paternalistik di Kabupaten Sarolangun, Provinsi Jambi - Al-Fikri, Albert (JURNAL AT-TURAS, 2018)
This study attempts to figure out the practice of inheritance of Muslim communities in Serolangun, Jambi, and its contestation with the discourses of maternalism and paternalism. The proponents of maternalism suggest that practice of inheritance is based on the law of tradition, while proponents of paternalism suggest the significance of relationship between inheritence and law of shariah. For the former, the right of having inheritence belongs to heiress, while the later insisted that shariah has ruled the two-equal to-one (2:1) between men and women. The contradiction between both groups indicates the dialectics of an-taradin based inheritence. This idea is derived from ridha (willingness) expressed explicitly or practiced implicitly by Serolangun people in the system of their inheritence. The an-taradhin is third way to integrate the maternalistic and paternalistic based inheritences by accomodating and providing win-to-win solution between the two groups.